2023
DOI: 10.7759/cureus.37547
|View full text |Cite
|
Sign up to set email alerts
|

A Case of COVID-19-Associated Focal Segmental Glomerulosclerosis

Abstract: This case report details a 43-year-old female diagnosed with the collapsing variant of focal segmental glomerulosclerosis (FSGS) post-infection with coronavirus disease 2019 . The patient contracted COVID-19 after returning from a trip to Florida and initially presented to the emergency department with gastrointestinal symptoms. Thereafter, the patient was diagnosed with COVID-19 and was admitted for acute kidney injury and worsening COVID-19 infection. FSGS is a glomerulopathy that consists of glomerular scar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…The TRPC6 protein is a 6-times transmembrane protein composed of 931 amino acids. The small pore region between its 5th and 6th transmembrane proteins forms the cation channel [8.9] The podocytes are cross-linked with each other to form a finger-like cross-linked fence-like structure called the lacunar pore, which is covered with a 4-6 nm film called the lacunar membrane SD.Recent studies have shown that podocytes are one of the important cells that make up the glomerular basement membrane [10] ,and abnormalities in the morphology, number and function of podocytes caused by various injury factors can cause proteinuria and eventually lead to renal function impairment [11][12][13] .Podocytes likewise play an important role in renal diabetic neuropathy, and many studies have demonstrated that podocyte loss and death are the earliest glomerular manifestations of renal diabetes [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The TRPC6 protein is a 6-times transmembrane protein composed of 931 amino acids. The small pore region between its 5th and 6th transmembrane proteins forms the cation channel [8.9] The podocytes are cross-linked with each other to form a finger-like cross-linked fence-like structure called the lacunar pore, which is covered with a 4-6 nm film called the lacunar membrane SD.Recent studies have shown that podocytes are one of the important cells that make up the glomerular basement membrane [10] ,and abnormalities in the morphology, number and function of podocytes caused by various injury factors can cause proteinuria and eventually lead to renal function impairment [11][12][13] .Podocytes likewise play an important role in renal diabetic neuropathy, and many studies have demonstrated that podocyte loss and death are the earliest glomerular manifestations of renal diabetes [14][15][16].…”
Section: Introductionmentioning
confidence: 99%